The Concise Oxford Dictionary of Linguistics - Matthews, P. H. (New York Oxford University Press, 2014)
The third edition of this dictionary is an authoritative and invaluable reference source covering every aspect of its wide-ranging field. It spans grammar, phonetics, semantics, languages (spoken and written), dialects, and sociolinguistics. Clear examples--and diagrams where appropriate--help to convey the meanings of even the most technical terms. It also incorporates entries on key scholars of linguistics, both ancient and modern, summarising their specialisms and achievements.
Keywords: Linguistics